Journal : Pitching Explosives: A Short History of Avalaunchers - John Brennan (International Society of Explosives Engineers, 2007)
OK, I’ll admit it: I’ve always been a big Monty Atwater fan. Not only is the man credited with being the father of modern avalanche forecasting and safety in the United States, but he is also responsible for developing the avalauncher. Through its more than 40-year history, the avalauncher has gone through many changes yet continues to prove its worth in avalanche mitigation work.